The Influence of Perceived Supervisor Support on Turnover Intention Mediated by Work Engagement : (A Study on Employees of PT. BPR Bali Dananiaga) (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The high level of Turnover Intention in regional banking industries indicates the importance of supervisor support in retaining employees. This study aims to analyze the effect of Perceived Supervisor Support on Turnover Intention with Work Engagement as a mediating variable. The research was conducted at PT BPR Bali Dananiaga involving 54 respondents selected using the purposive sampling method. Data were collected through questionnaires and analyzed using Path Analysis, Classical Assumption Tests, and the Sobel Test. The results show that Perceived Supervisor Support has a significant negative effect on Turnover Intention, Perceived Supervisor Support has a significant positive effect on Work Engagement, Work Engagement has a significant negative effect on Turnover Intention, and Work Engagement significantly mediates the effect of Perceived Supervisor Support on Turnover Intention. These findings strengthen Social Exchange Theory, stating that reciprocal relationships between supervisors and employees increase work engagement and reduce the intention to leave the organization.